Financial institutions management : a risk management approach - Saunders, Anthony , 1949-; Cornett, Marcia Millon (The McGraw-Hill/Irwin series in finance, insurance, and real estate, 2011)
Provides an approach that focuses on managing return and risk in modern financial institutions. The central theme of this book, is that the risks faced by financial institutions managers and the methods and markets through which these risks are managed are becoming increasingly similar whether a commercial bank, a savings or an investment bank